Evaluación de Desempeño del Talento Humano del Sindicato de Choferes Profesionales del cantón Paltas, provincia de Loja, periodo 2024 - Rodríguez Saraguro, Diana Mabel (2025)
This Curricular Integration Work analyzes the performance evaluation process of the union's administrative and operational personnel. Using a mixed methodology that includes historical, inductive, deductive and analytical methods, as well as survey techniques, interviews and direct observation, the study identifies strengths and weaknesses in the management of human talent. The survey was applied to employees of the Sindicato de Choferes Profesionales del Cantón Paltas, whose sample consisted of seven employees who work permanently in the organization. The survey revealed that 71% of the employees perceive that they receive support from their immediate boss, although only half consider internal communication “completely clear and effective. Eighty-six percent rated the evaluation method as excellent, highlighting the general acceptance of the process. However, a need to improve constant feedback was identified, as only 14% receive regular feedback on their performance. In addition, it was evident that the majority of respondents perceive professional growth opportunities positively, although only 14% consider them “very good”. Key areas for improvement include communication, feedback and the development of teamwork skills. The findings highlight the need to improve internal union communication, feedback and professional development opportunities within the institution. Based on the results, a performance evaluation model is proposed to optimize operational efficiency, increase job satisfaction and improve the quality of service offered by the organization